(untitled) (Eurasian Medical Research Periodical, 2022)
To study the clinical course of acute myocardial infarction (MI) with ST segment elevation and features of inpatient treatment in patients with diabetes mellitus diabetes and without it. Material and methods: 83 patients admitted to hospital in 2014 were included. Patients were divided into two groups depending on the presence or absence of carbohydrate metabolism disorders: group 1 (patients with type 2 diabetes; n=38) and group 2 (patients without carbohydrate metabolism disorders; n=45). We studied the initial clinical, demographic and laboratory-instrumental characteristics of patients, as well as the features of inpatient treatment. Results: In group 1, compared with group 2, arterial hypertension was significantly more often recorded (73.7% vs. 49%; p <0.05), patients in group 1 had higher class of acute heart failure according to the Killip classification at admission (1.46±0.6 vs. 1.23±0.57; p><0.05). STEMI in patients of group 1 by 12% more often complicated by the development of acute aneurysm of the left ventricle (p><0.05). The duration of inpatient treatment of patients in group 1 was longer (18±4.1 vs. 16±3.6 days; p><0.05). Conclusion. Only 21% of diabetic patients hospitalized for STEMI received adequate treatment for coronary heart disease, and a quarter of this group did not have adequate therapy for diabetes. Patients with DM had a higher incidence of in-hospital complications of STEMI and a longer duration of inpatient treatment>